CHARACTER BUILDING ACHIEVEMENT THROUGH EDP’S ACTIVITY: SEEKING AND INVITING NATIVE SPEAKER - Fatimah Fatimah; Hayati Syafri (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
This paper is aimed to reveal the character building achievement gotten from one of EDP’s activities: seeking and inviting native speaker to the campus done by the EFL students in STAIN Bukittinggi. In this activity, the students get along with them and enjoy practicing their English automatically. This activity is useful to build up students’ courage, students’ self-confidence, students’ self-esteem, and overcoming students’ anxiety to speak English. Especially in Bukittinggi that has many tourism objects and visitors from all over the world, there is always a big chance for the ELS students to meet and talk with native speakers. When they have the brave to talk face to face with native speakers, they directly have built up their courage to speak English. Besides, the other characters (having self-confidence, having self-esteem, and overcoming the anxiety) are built up as well. Moreover, through the activity of seeking and inviting native speakers providing by EDP, the ELS students are not only active to practice their English but also have chance to build up their characters. They look for native speakers, greet them, talk to them, and take them to walk around together. Finally, this activity is really effective to build up character and improve their speaking skill. Keywords: Character Building, Seeking and Inviting Native Speaker